Perlindungan Hukum Terhadap Anak Korban Kekerasan Fisik Oleh Orang Tua Kandung - Muhammad Iqbal; Syaiful Asmi Hasibuan; Sumarno Sumarno (Jurnal Hukum dan Sosial Politik, 2023)
The purpose of this research is to analyze the legal protection of child victims of physical violence by biological parents. This research uses a literature review approach by looking for theoretical references that are relevant to the case or problem found. Based on the results and discussion, it is found that the forms of violence experienced by children are physical violence such as: being kicked, hit, thrown with wood, slapped and even hung, resulting in children feeling depressed by the violence they experience and children who experience this rarely communicate with their friends. The sources that trigger physical violence against children are poverty, violence also occurs because the parents are stressed or have complicated problems. Parents' lack of knowledge The existence of children who do not want.